ERRORS IN DIAGNOSIS AND TREATMENT OF CHRONIC OSTEOMYELITIS ALVEOLAR BONE - Лепський В. В. (World of Medicine and Biology, 2015)
In most cases, chronic osteomyelitis alveolar bone is a complication of acute odontogenic process: acute periodontitis, acute sinusitis, cystic cavity suppuration, acute pericoronitis or acute osteomyelitis. Mandible is affected more frequently. Late or insufficient effective treatment of acute process facilitates the transition of acute to subacute process, and then a phase of chronic inflammation of the jaw [1,2]. Obviously, diagnose patients with subacute osteomyelitis is possible only when recently he had a high fever, intoxication, the corresponding picture of the blood, other indicators that are typical for acute osteomyelitis. The process of gradual reduction of these indications fit in the concept of sub-acute inflammatory process [1, 2]. Bacteriological examination of pus and granulation tissue in chronic odontogenic osteomyelitis of the jaws often reveals a mixed microflora: staphylococci, streptococci, Proteus, spirillum Vincent et al., With the prevalence of Staphylococcus [4]. Clinically, chronic osteomyelitis alveolar process occurs not difficult: patients complain of the presence of one or more of the fistula in the mouth with purulent discharge. Overall condition is not violated, the temperature of the reaction there. Apparently, therefore, doctors, dentists, not the patient radiologically surveyed and found out quite clearly the dynamics of the disease immediately make surgery: scrape granulation of fistula, prescribe antibiotics, anti-inflammatory drugs. Such manipulation can improve the condition of the patient for 2-3 days, and then the pus begins to stand out even more in the process does not stop, on the contrary, there may be other fistula with purulent discharge [3,5]. Errors in diagnosis, patient care, early surgical intervention were the purpose of a more thorough investigation of this pathology. Objects and methods of research. We observed in the surgical department of the clinic were 8 patients with chronic osteomyelitis of the mandible alveolar process. Patients ranged in age from 23 to 54 years, four men and four women. Results of the study. All patients complained of the presence of a fistula with purulent discharge. From the history of the disease found that two men cause of fistula was complicated removal of third molars, two patients abscess has been opened, but, apparently, the cut was not enough, as the pus continued to stand out from the wound, and then it dropped and in its place He formed a fistula. Four women were untimely opened abscess, after opening the abscess soon appeared fistula with purulent discharge. An objective study patients configuration person usually has not been changed, the skin of normal color. Palpable determined enlarged, painless lymph nodes in the submandibular region corresponding side. Opening the mouth free. Oral mucosa pale pink, round fistula slightly changed in color, the hyperemic. Fistulas all patients were placed from the vestibular surface with 6 patients in the area of missing teeth that were removed earlier, two - in the area of 3.5 and 3.6 of the teeth, the teeth slightly movable (I-II cent.), Of the fistula stood thick pus when sensing a fistula probe rests on the fixed wall of the bone. All patients underwent blood tests, X-ray of the alveolar bone in the affected area, two patients - computer tomography 3D. On radiographs of all patients revealed bone destruction in the form of lines surrounding one or another portion of the bone, but completely the affected area was not surrounded by a line of destruction, which indicated that the lifeless section of bone is not yet fully separated granulation tissue from healthy bones. In this condition, bone surgery is contraindicated, as would contribute to the spread of inflammation on bone health. In this patient’s disease is a stimulation therapy: intramuscular injection of vitamin B1 and B12 1.0 ml №10, / m in a day; aloe, FIBS, vitreous placenta 1 ml №10 daily; autohaemotherapy scheme (from 2.0 ml to 10.0 ml from 10 ml to 2.0 ml - 2 times a week intramuscularly); physiotherapy (UHF number 10). After the treatment of clinically fistula nothing stood out or were scarce sukrovichnye allocation; Four patients reported that on the eve of the fistula was allocated more dense bone areas. When probing fistulas movable bone formation were determined in four patients. Patients were re-held X-ray examination, which reveals that the line of destruction completely surrounds the affected area of bone or determinable small sequesters.